Moderating Role of Religious Orientation in the Relationship of Perceived Mental Illness Stigma and Suicidal Ideation Among Filipino Young Adults - Caparas, Hanna Mae; Llenares, Ian (Journal of Interdisciplinary Perspectives, 2025)
Due to underreported suicide cases and increasing mental health issues, the study examined the relationship between perceived mental illness stigma and suicidal ideation among young adults in a religious country like the Philippines, focusing on the moderating role of religious orientation. Through quantitative research employing a moderation model, 137 Filipino young adults working in private Catholic schools in Bulacan were purposively sampled. Three standardized questionnaires were adapted. Results revealed that perceived mental illness stigma was present at a below-average level. Suicidal ideation levels were generally very low over the year, but some participants had already experienced it from a young age. Filipino young adults exhibited high extrinsic and low intrinsic religious orientations. Using Pearson's correlation, findings indicated a positive significant relationship between perceived mental illness stigma and suicidal ideation, suggesting that higher levels of perceived stigma were linked to increased suicidal thoughts. As individuals perceive that they will be devalued and discriminated against for having a mental illness, there is also a higher tendency for them to be preoccupied with suicidal thoughts. However, the result of Hayes Process moderation analysis shows that neither extrinsic nor intrinsic religious orientation has an interaction effect with perceived mental illness stigma on suicidal ideation. The absence of interaction effect indicates that the correlation between the perceived stigma of having a mental illness and having suicidal thoughts remained consistent regardless of the religious orientation of Filipino young adults. Since it focused on a single religious group, the findings cannot be generalized due to sampling limitations.